Physiological and Immunological Disturbance in Rheumatoid Arthritis Patients (Baghdad Science Journal, 2021)
Rheumatoid arthritis (RA) is a systematic autoimmune disorder with chronic inﬂammation changes of unknown etiology. Various synovial inﬂammatory and proliferative alterations may contribute to the cartilaginous tissues and invasive bony tissues, leading to destructive joints and malformed bones. This disease is mostly due to infective microorganisms or genetic susceptibility causing immune system disturbances through triggering both T-cells and B-cells. Furthermore, different immune cells may secret cytokines, which are responsible for some RA pathogenesis activity. From ninety individuals, serum sample was collected; thirty of them were normal and sixty cases were patients with RA attended a privet medical clinic at Tikrit city from May 2019 to November 2019. Age, in both patients and control groups, ranged between (18-50) years, they had assay of Interleukin-1 (IL-1), Interleukin-6 (IL-6), Interleukin-10 (IL-10), Tumor necrosis factor (TNF)-α, Leptin, Adiponectin, and C-reactive protein. The present study shows that (IL-1, Leptin, and CRP) levels were higher in Rheumatoid Arthritis patients than control, while (IL-6, IL-10, TNFα, and ADP) levels were lower; therefore, cytokines can play an essential role in RA pathogenesis. The current study may bring attention to adiponectin and leptin for their roles in the pathogenesis of RA. Special consideration was devoted to those proteins, which act on cells associated with RA, also for possible usage of these protein levels as potential biomarkers for the disease activity and therapeutic response.